PERANCANGAN SISTEM SCADA (SUPERVISORY CONTROL AND DATA ACQUISITION) PADA MESIN BOILER 21 TON PIPA API DI PT. INDOFOOD DIVISI NOODLE SEMARANG (Science and Technology (SciTech), 2023)
Boiler machines play a crucial role in the food and beverage industry, including at PT. Indofood Divisi Noodle Semarang. This research aims to design and implement a Supervisory Control And Data Acquisition (SCADA) system for a 21-ton fire tube boiler at PT. Indofood Divisi Noodle Semarang to enhance supervision, control, and operational safety. The research methodology involves surveying the existing boiler system, identifying effective monitoring and control requirements, and designing and implementing a suitable SCADA system. Data collection methods include literature review, interviews, and direct observation about of the boiler machine. Operational parameters, required sensors, and monitoring and control tasks are identified as part of the data collection process. The research results in the design of an integrated SCADA system for the 21-ton fire tube boiler at PT. Indofood Divisi Noodle Semarang. The SCADA system consists of a central monitoring unit with an intuitive user interface, sensors and instruments for data collection, secure communication for data transmission, and a centralized database. The SCADA system enables supervisors to monitor real-time operational conditions, control desired operational parameters, and analyze historical data for early problem detection. The implementation of the SCADA system on the boiler machine provides significant benefits. Real-time supervision allows for early detection of operational issues, reducing production downtime, and minimizing losses. Automatic control helps maintain optimal operational conditions and improves efficiency. The SCADA system also provides enhanced security through advanced security technologies.